The association between vitamin K status and knee osteoarthritis features in older adults: The Health, Aging and Body Composition Study. Issue 3 (March 2015) - Shea, M.K.; Kritchevsky, S.B.; Hsu, F.-C.; Nevitt, M.; Booth, S.L.; Kwoh, C.K.; McAlindon, T.E.; Vermeer, C.; Drummen, N.; Harris, T.B.; Womack, C.; Loeser, R.F.; et al.
Summary: Background: Vitamin K-dependent (VKD) proteins, including the mineralization inhibitor matrix-gla protein (MGP), are found in joint tissues including cartilage and bone. Previous studies suggest low vitamin K status is associated with higher osteoarthritis (OA) prevalence and incidence. Objective: To clarify what joint tissues vitamin K is relevant to in OA, we investigated the cross-sectional and longitudinal association between vitamin K status and knee OA structural features measured using magnetic resonance imaging (MRI). Methods: Plasma phylloquinone (PK, vitamin K1) and dephosphorylated-uncarboxylated MGP ((dp)ucMGP) were measured in 791 older community-dwelling adults who had bilateral knee MRIs (mean ± SD age = 74 ± 3 y; 67% female). The adjusted odds ratios (and 95% confidence intervals) [OR (95%CI)] for presence and progression of knee OA features according to vitamin K status were calculated using marginal models with generalized estimating equations (GEEs), adjusted for age, sex, body mass index (BMI), triglycerides and other pertinent confounders. Results: Longitudinally, participants with very low plasma PK (<0.2 nM) were more likely to have articular cartilage and meniscus damage progression after 3 years [OR (95% CIs): 1.7(1.0–3.0), 2.6(1.3–5.2) respectively] compared to sufficient PK (≥1.0 nM). Higher plasma (dp)ucMGP (reflective of lower vitamin K status) was associated with higher odds of meniscus damage, osteophytes, bone marrow lesions, and subarticular cysts cross-sectionally [ORs (95% CIs) comparing highest to lowest quartile: 1.6(1.1–2.3); 1.7(1.1–2.5); 1.9(1.3–2.8); 1.5(1.0–2.1), respectively]. Conclusion: Community-dwelling men and women with very low plasma PK were more likely to have progression of articular cartilage and meniscus damage. Plasma (dp)ucMGP was associated with presence of knee OA features but not progression. Future studies are needed to clarify mechanisms underlying vitamin Ks role in OA.